Carving out another slice of the pie: Exceptional response to single agent imatinib in an asian female never-smoker with advanced NSCLC with a de-novo PDGFR-α N848 K mutation. (October 2018) - Klempner, Samuel J.; Gowen, Kyle; Lee, Thomas K.; Zhu, Viola W.; Schrock, Alexa B.; Miller, Vincent A.; Ali, Siraj M.; Ou, Sai-Hong Ignatius
Highlights: PDGFRA N848 K is a rare mutation in NSCLC and analogous to the imatinib-sensitive N822 K KIT mutation in GIST. PDGFRA N848 K represents and rare but actionable variant in advanced NSCLC. Ongoing broad genomic profiling is important to continue identification of rare variants in NSCLC. Abstract: Non-small cell lung cancer (NSCLC) has emerged as a paradigm for clinical application of precision medicine as optimal therapy is commonly chosen based on genomic biomarkers identified in a patient's tumor sample. Recurrent driver alterations are well described, however, a need to continually identify rare variants remains clinically relevant. We identified an incident case of advanced NSCLC with a PDGFR-α N848 K activation loop mutation with no other concurrent oncogenic drivers. Amino acid sequence alignment confirmed homology to the imatinib-sensitive KIT N822 K activation loop mutation observed in GIST. The patient achieved a 2-year response to single agent imatinib that is ongoing. While PDGFR-α N848 K is rare among public sequencing databases our cases strongly suggests functional relevance and highlights the importance of studying rare variants in NSCLC.